Short- and long-term comparative effectiveness of nirmatrelvir/ritonavir and molnupiravir in asthma patients: a cohort study - Guozhang Lin; Yuchen Wei; Zihao Guo; Huwen Wang; Kate Ching Ching Chan; Renee Wan Yi Chan; Chi Tim Hung; Xiaoting Jiang; Conglu Li; Carrie Ho Kwan Yam; Tsz Yu Chow; Yawen Wang; et al. (Respiratory Research)
Abstract Background Few studies evaluated the effectiveness of COVID-19 antivirals specifically in the asthma population This study assessed short- and long-term effects of nirmatrelvir/ritonavir versus molnupiravir in asthma population. Methods This is a retrospective cohort study on adult asthma patients infected with COVID-19, using real-world data obtained from the health officials in Hong Kong. Key inclusion criteria were infection with COVID-19 between March 16, 2022, and Oct 30, 2023, age ≥ 18 years, previous asthma diagnosis, and prescription history of an asthma medication. Outcomes included acute and post-acute mortality, post-acute all-cause hospitalization, and cause-specific hospitalization. Results 1,745 patients were eligible for this study, with a median follow-up time of 365 days (IQR: 335–365). Patients in the nirmatrelvir/ritonavir group had significantly lower risks of acute inpatient death (HR, 0·27 [95% CI, 0·12 to 0·59]; p = 0·0011), post-acute inpatient death (HR, 0·49 [95% CI, 0·28 to 0·85]; p = 0·011), all-cause hospitalization (HR, 0·72 [95% CI, 0·58 to 0·89]; p = 0·0020), and myocardial infarction (HR, 0·10 [95% CI, 0·01 to 0·92]; p = 0·042) than patients in the control group. The risk of all-cause hospitalization was significantly lower in the nirmatrelvir/ritonavir group compared to the molnupiravir group (HR, 0·65 [95% CI, 0·52 to 0·81]; p = 0·00012). Among patients who were prescribed medium-/ high-dose inhaled corticosteroids, the nirmatrelvir/ritonavir group had a lower hazard of asthma exacerbation than the molnupiravir group (HR, 0·58 [95% CI, 0·35 to 0·95]; p = 0.030). Conclusion Compared with molnupiravir, nirmatrelvir/ritonavir may offer more benefits in reducing the risk of post-acute sequelae of COVID-19 among asthma patients. In addition, the post-acute benefits of the antivirals were also demonstrated in patients with mild asthma, which have not been generally recommended in existing clinical management guidelines.